GUILD: AN AID IN IMPROVING THE GRADE 10 STUDENTS’ PERFORMANCE IN CALCULATING PROBLEMS IN VAPOR PRESSURE LOWERING - ZINAMPAN, JOAN (International Journal of Arts, Sciences and Education, 2021)
This study aimed to look into the effectiveness of Guided Inquiry-based Learning Design in calculating problems in vapor pressure lowering to Grade 10 students. Using Quasi-Experimental research design, two groups were given a pretest on vapor pressure lowering. The experimental group of 18 students, was exposed to the guided inquiry-based learning design method; the control group of 17 students was exposed to the traditional way of teaching. The post test was administered after five (5) class sessions. Using Independent Samples t-test, the computed p-value is 0.026, which is lesser than the significance level, 0.05. Therefore, there is a significant difference on the post-test scores between the experimental and the control group. This is an indication that the performance of the students being exposed to Guided Inquiry-based Learning Design is better than the students under the traditional method.